Pelaksanaan proses pengauditan kualiti: Di sebuah Jabatan Pendidikan Negeri / Azizan Zamhari - Azizan, Zamhari (2017)
This study researched the implementation of auditing processes and quality in Selangor State Education Department (NRD) of Selangor. The researcher form a conceptual based, while referring to the Audit Process Model, the Audit Quality Management System (QMS) ISO 9001: 2008 and CIPP Model. The data obtained through questionnaires were answered by 370 officers Group management team, staff, and employees of the Group Implementation Assistant. The research aims to study about the process of an audit Quality Management System (QMS) ISO 9001: 2008. The study also reviewed the level of conformity in implementation of quality auditing process. The level of conformity was measured by nine (9) domains in audit process issued by SIRIM. The data obtained through questionnaires were answered by 345 staff members of the State Education Department, 25 officers and employees of the District Education Office (DEO) that were randomly selected and interviews of over 12 respondents. Descriptive analysis, namely demographic profile top of respondents show a high level of compliance is for domains Audit Planning followed by Input and Output Domains.(However, the level of conformity employees in the audit process is moderate). Mean scores indicate the domain value Equipment is the highest 4.5363, followed by domain checklist and Measurement Criteria. This shows the three main domains dominated and were understood by employees in the auditing process. Sample t-test shows the difference Test conformity level between males and females is for the domain checklist and Output. One way ANOVA showed the highest level of conformity in the audit was for the Group's officers, followed by the Management Group staff, and on Implementation was General Assistant Group staff. Multiple Regression analysis showed the male staff has the level of conformity of .125 more than female employees, the level of conformity in the process of auditing for an employee who has more than 20 years experience was less than .432 for experienced staff between 6 to 10 years. In addition, the level of conformity for an employee who holds a Bachelor's degree was 498 higher than the employees whose qualifications are at the Bachelor level. The level of conformity for an employee who holds a Bachelor's degree was higher than 266 for the staff whose qualifications are Diploma. The findings of the interview session with 12 respondents indicate that there is collaboration in implementing the auditing and all the challenges can be well overcome. Research outcome is also applicable to enhance the audit routine practice by JPN Selangor